Próba nakreślenia teorii konferencji jako pedagogiczno-artystycznego widowiska kulturowego. Na przykładzie przebiegu konferencji „Od inspiracji do kreacji. Wyzwania edukacyjne i artystyczne” - Dembiński , Mariusz (Studia Edukacyjne, 2021)
The aim of the article is an attempt to outline the theory of the conference (scientific), taking into account its actual course, including the reported content, as the ontic basis of its real structure. At the heart of this concept is a myth whose stories form the basis for the emergence of cultural spectacles. In the case of a conference conceived as a spectacle, the founding form (myth) is skholé. The conference itself is shaped in two overlapping areas: firstly, it is subject to the process of ritualization, and secondly, it is subject to the coexistence of universal praxis. In view of the subject of the conference mentioned and analyzed here, this theory takes into account aesthetic and pedagogical interactions (principles), ignoring others (ethics, economy, politics, religion). The conference theory should contribute to the understanding of its coherent thinking and operation structure; the importance of its impact on its participants, the legitimacy of its organization and study; the possibility of consciously shaping its course, in the cognitive - methodological context (I omit the otherwise important socio-cultural aspects).